Medical Student-Run Free Orthopaedic Clinic: Impact of Coordinator Role on Specialty Selection - Koetter, Paige; Thomas, Rachel; Gallo, Robert (Journal of Student-Run Clinics, 2023)
Background: Medical student-run free clinics provide opportunities for future physicians to accrue practical experience early in their medical education. Subspecialty clinics including orthopaedics provide a unique opportunity to gain exposure to musculoskeletal anatomy and pathology. These clinics are organized and managed by a student clinic coordinator. In this study, we seek to understand the impact that being the clinic coordinator of the musculoskeletal clinic plays in specialty selection. Methods: A descriptive study was conducted by gathering electronic survey responses from former student clinic coordinators at the Penn State College of Medicine student-run musculoskeletal clinic from years, 2009 to 2017. The respondents described the influence of the coordinator role on residency selection. Additionally, the survey consisted of a five-point Likert scale ranging from 1 (strongly disagree) to 5 (strongly agree) regarding the student’s motivation for participating in the clinic as a coordinator. Results: From 2009 to 2017, there were 18 LionCare Orthopaedic Surgery Clinic Coordinators with a male-to-female ratio was 1.25:1. Residency specialty selection was Orthopaedic Surgery (n=8, 44.4%), Physical Medicine & Rehabilitation (4, 22.2%), Family Medicine (2, 11.1%), Cardiothoracic Surgery (1, 5.6%), General Surgery (1, 5.6%), Obstetrics & Gynecology (1, 5.6%), and Emergency Medicine (1, 5.6%). The most commonly cited reason for participation as clinic coordinator was “interest in helping an underserved population.” Conclusions: The study illustrates an association between the role of orthopaedic clinic coordinator and entering a specialty focused on musculoskeletal care. More than half of the students who participated as a clinic coordinator pursued specialties involving musculoskeletal care (Orthopaedics and Physical Medicine & Rehabilitation). Student-run medical clinics present an opportunity to provide early exposure to musculoskeletal medicine and potential avenue for orthopaedic education and mentorship.